Combined effects of quinic acid and isochlorogenic acid B on LPS-induced inflammation and pyroptosis in MAC-T cells and mouse mammary glands - Lv, Xiang; Long, Quan; Kang, Yuchen; Lin, Tao; Jiang, Caode (Frontiers in Veterinary Science, 2025)
IntroductionQuinic acid (QA) and isochlorogenic acid B (ICAB) have been demonstrated to possess antioxidant, anticancer, and anti-inflammatory properties. However, their combined efficacy in protection against mastitis requires further investigation. This study aims to examine the inhibitory effects and mechanisms of QA and ICAB combination on lipopolysaccharide (LPS)-induced inflammation and pyroptosis in bovine mammary epithelial cells (MAC-T) and mouse mammary tissue.MethodsThe optimal concentrations of QA and ICAB for treating MAC-T cells were determined using Cell Counting Kit-8 (CCK-8). Expression levels of inflammatory factors, oxidative stress and pyroptosis indicators were assessed by ELISA. Immunohistochemistry was employed to detect CD3 levels in mouse mammary glands, while Western blot and immunofluorescence techniques were used to measure the expression levels of NOD-like receptor 3 (NLRP3) inflammasome, caspase-11, gasdermin D (GSDMD), and p65 of nuclear factor κB (NF-κB) in MAC-T cells.ResultsQA (60 μg/mL) and ICAB (20 μg/mL) co-treatment significantly enhanced MAC-T cell activity (p < 0.05). Combined treatment of QA and ICAB significantly decreased the expression of LPS-induced inflammatory factors (TNF-α, IL-1β, and IL-6) and oxidative stress factors (COX-2 and iNOS) in both MAC-T cells and mouse mammary glands (p < 0.05), and dose-dependently lowered the levels of pyroptosis indicators (ROS, LDH, and IL-18) (p < 0.05). After intraperitoneal injection of QA (20 mg/kg) and ICAB (5 mg/kg), LPS-treated mice exhibited significantly reduced expression of CD3 (p < 0.05) and decreased T lymphocyte infiltration in the mammary gland, with a pronounced effect compared to QA and ICAB treatment alone. The combined administration of QA and ICAB also effectively suppressed the expression levels of NF-κB (IκBα, p65, p-IκBα, and p-p65) induced by LPS in MAC-T cells and mouse mammary glands, as well as the nuclear translocation of NF-κB in MAC-T cells (p < 0.05). Furthermore, the protein levels of NLRP3 inflammasome (NLRP3, ASC, and caspase-1), caspase-11, and GSDMD were significantly reduced (p < 0.05) compared to QA and ICAB treatment alone.ConclusionQA and ICAB synergistically inhibits the inflammatory response and pyroptosis in MAC-T cells and mouse mammary glands through modulation of NF-κB pathway and NLRP3 inflammasome. This study contributes novel insights into combination of QA and ICAB in the prevention and treatment of mastitis.